Computer-aided manufacturing training using Tukatech software - UiTM, Fakulti Sains Gunaan (Faculty of Applied Sciences, 2020)
A Computer-Aided Manufacturing training using Tukatech Software was held at Apparel Lab in FSG. The training was organized by the Department of Textile Science & Fashion Technology on September 3rd until 9th 2020. The objectives of the training were to give exposure to the important features of Tukatech software and to demonstrate how to use its application in garment manufacturing. CAM Implementation in the Apparel Industry Computer-Aided Manufacturing is an automation system that designs, regulates, and determines control of production operations.